Manhaj Ulama Salaf dalam Menjaga Kemurnian Aqidah Islam Perspektif Salafi Tentang Tawassul Kontemporer Studi Keislaman - Nabila Julianda Sapitri; Atik Rahmawati; Denistianah Habibah (CV. Doki Course and Training, 2026)
ABSTRACT The methodology (manhaj) of the salaf scholars plays a central role in preserving the purity of Islamic creed by upholding the Qur’an and Sunnah as the primary sources of guidance and exercising caution in matters of belief and worship. This article examines the salafi methodology by exploring the dynamics of salafi thought, the differences between the approaches of the salaf and khalaf, the concept of salaf according to Imam Ahmad ibn Hanbal and Ibn Taymiyyah, as well as the discourse on tawassul from a hadith perspective. Using a qualitative library research approach, the study finds that the salaf methodology is founded upon three main principles: the purification of tawhid, adherence to textual evidence (nass), and caution toward religious practices lacking clear proof. In the discussion of tawassul, salaf scholars emphasize the authenticity of hadith and restrict practices that may compromise the purity of creed. This article highlights the continued relevance of the salaf methodology in addressing contemporary theological and religious challenges. ABSTRAK Manhaj ulama salaf berperan penting dalam menjaga kemurnian aqidah dengan menjadikan Al-Qur’an dan sunnah sebagai rujukan utama serta bersikap hati-hati dalam persoalan keyakinan dan ibadah. Artikel ini mengkaji manhaj salaf melalui dinamika pemikiran salafi, perbedaan pendekatan salaf dan khalaf, konsep salaf menurut Imam Ahmad bin Hanbal dan Ibnu Taimiyah, serta pembahasan tawassul dalam perspektif hadis. Dengan metode kualitatif studi pustaka, penelitian ini menemukan bahwa manhaj salaf bertumpu pada pemurnian tauhid, kepatuhan pada nash, dan kehati-hatian terhadap praktik tanpa dalil yang jelas. Dalam isu tawassul, ulama salaf menekankan validitas hadis dan pembatasan praktik yang berpotensi menyimpang dari aqidah. Artikel ini menegaskan relevansi manhaj salaf dalam menjawab tantangan teologis masa kini.